Motivasi Belajar Bahasa Arab Pada Siswa SMK Muhmmadiyah 2 Ngawi - 1Andreyas Istiqomah; Muwahidah Nurhasanah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2021)
In this era of Arabic language is less attractive to students to learn, the fundamental problem is the difficulty of them in understanding arabic texts. Because it is a foreign language, so they rarely encounter it every day. Therefore, a teacher needs to make efforts that can arouse students to learn Arabic. These motivations include approaches, methods and strategies used in classroom learning activities. Of course, in trying to do so must go through various considerations so as not to make it difficult for students to follow it. Therefore, with these efforts are expected to arouse the interest of students in learning Arabic so that Arabic language is no less interested.